2020
DOI: 10.1186/s13223-020-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Replication study of susceptibility variants associated with allergic rhinitis and allergy in Han Chinese

Abstract: Background: Allergic rhinitis (AR) is believed to be a complex genetic disease. The last decade has been marked by the publication of more than 20 genome-wide association studies (GWASs) of AR and associated allergic phenotypes and allergic diseases, which have shown allergic diseases and traits to share a large number of genetic susceptibility loci. The aim of present study was therefore to investigate the highly replicated allergy related genes and variants as candidates for AR in Han Chinese subjects. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Among them, rs62026376 C allele was observed to be associated with an increased risk of hay fever asthma. In addition, Gao et al noticed that CLEC16A rs7203459 was a specific susceptibility locus of AR in the Han Chinese population (Gao et al, 2020). In our research, we also observed the significant association between CLEC16A SNPs (rs2286973, rs887864, rs12935657, rs11645657 and rs36045143) and AR risk.…”
Section: Discussionsupporting
confidence: 82%
“…Among them, rs62026376 C allele was observed to be associated with an increased risk of hay fever asthma. In addition, Gao et al noticed that CLEC16A rs7203459 was a specific susceptibility locus of AR in the Han Chinese population (Gao et al, 2020). In our research, we also observed the significant association between CLEC16A SNPs (rs2286973, rs887864, rs12935657, rs11645657 and rs36045143) and AR risk.…”
Section: Discussionsupporting
confidence: 82%
“…Studies of GWAS data combined with functional annotations and quantitative trait loci (QTL) have sought to strengthen their context-specific relevance. In addition to replicating previously known loci, new candidate genes including DGKQ, SLC26A1 , and IDUA genes, as well as variants of genes encoding transcription factors like NF-KB , cJUN , STAT family, ERG1 , ELF1 , EBF1 , and the GATA family have been identified ( 32 35 ). Atopy-associated GWAS have identified multiple relevant biological pathways, including autoimmune and inflammatory response pathways, thereby providing insights into the underlying heritable risk ( 31 , 36 ).…”
Section: Gwas Discovery Of Asthma Associated Genetic Linkagesmentioning
confidence: 90%
“…signal transduction and apoptosis, and it has been associated with asthma and allergy [120–122 ]. In recent candidate gene analysis in Han Chinese population, it has been shown to associate with AR [123 ]. In vitro‐ studies show the involvement of WDR36 in G q ‐coupled muscarine, bradykinin and histamine receptor signaling [124 ], all of which are important modulators of allergic reactions and asthmatic bronchoconstriction.…”
Section: Literature Reviewmentioning
confidence: 99%